The Curtain Rises: Teachers Unveil Their Processes of Transformation in Doing Classroom Inquiry - Denise Fischer; Maria Mercado; Vicki Morgan; Lori Robb; Jacquelyn Sheehan-Carr (Networks: An Online Journal for Teacher Research, 2000)
This paper is the joint reflection of a group of teachers on their transformative process of engaging in a systematic inquiry in their own classrooms. While sharing and reconstructing their experiences, they found that most of them went from detachment and resistance, when they were introduced to the idea of teacher-research, to engagement in a community of inquirers, and to uncovering the unforeseen benefits of doing teacher-inquiry.